Deteksi Gen P14ARF Pada Spesimen Blok Parafin Lidah Penderita Karsinoma Sel Skuamosa Di RSUD Dr. Moewardi - Rakhmat, Jinan Fairuz Anindika; Subiyantoro, Pradipto; Nirmala A, Vita (Nexus Biomedika, 2013)
Background : The oral cavity cancer is twenty most common cancer that occurs in the world. Around  90%  oral cavity cancer cell carcinoma is squamous and most of the incidents come from tongue. p14ARF gene is one of the tumor suppressor gene that can prevent the occurrence of a tumor. The purpose of this research was to know the existence of p14ARF gene in paraffin block specimens of the tongue of the squamous cell carcinoma patients in the Regional Public Hospital Dr. Moewardi. Methods : This study was explorative and descriptive research. Paraffin block samples of the tongue squamous cell carcinoma patients were used in this study. The object of this research was p14ARF gene located on chromosomes 9p21. The samples were separated from the Paraffin Block and their DNA were isolated. The DNA products, then, were amplified by PCR and their PCR products were run in agarose gel electrophoresis. Later, the gel was visualized with Gel Documentation and analyzed to detect the  p14ARF gene. Results : On the visualisation of the gel product, the p14ARF gene was detected in one sample with atypical band pattern and it was not detected on the eight other samples. Conclusion : Only one sample of the tongue squamous cell carcinoma patients which was positive expressed p14ARF gene with atypical band pattern while the eight other samples were not. Keywords : tongue squamous cell carcinoma, p14ARF, oral cavity cancer